Viability and storage of Myrceugenia euosma (O. Berg) D. Legrand and Siphoneugena reitzii D. Legrand (Myrtaceae) pollen - Corrêa, Bruno Jan Schramm; Sá, Alexandra Cristina Schatz; Oliveira, Luciana Magda de; Mantovani, Adelar; Bortoluzzi, Roseli Lopes da Costa (Revista de Ciências Agroveterinárias, 2024)
This study evaluated aspects of the pollen viability of the species Myrceugenia euosma (O. Berg) D. Legrand and Siphoneugena reitzii D. Legrand (Myrtaceae), both native trees with ornamental, medicinal and industrial potential. The study used different concentrations of sucrose to determine pollen viability in vitro and through colorimetric tests with specific dyes (Lugol, carmine acetic, and tetrazolium chloride – TTC – 0.1 and 0.05%). The two species also had their pollen stored for 30 and 90 days in freezers, refrigerators, and natural environments to check the best method for preserving their viability. The results showed that the highest average germination of M. euosma pollen was in a culture medium containing 30% sucrose. After 30 and 90 days of storage, pollen viability was significantly reduced, having preserved part of its potential only in the freezer. The pollen of S. reitzii had a higher average germination rate in a medium with 20% sucrose, but also showed a reduction in viability after 30 and 90 days of storage. The colorimetric tests showed that the pollen of both species responded to the dyes. However, the viability of Lugol and carmine acetic was considered to be overestimated in relation to the in vitro germination tests. Tetrazolium at 0.1% proved to be an alternative for checking the viability of S. reitzii pollen. It can be concluded that different concentrations of sucrose affect germination, and that storing pollen at a low temperature can preserve some of its viability in the short term.